2019
DOI: 10.1001/jamainternmed.2018.5139
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Violent Injuries Unreported to Law Enforcement

Abstract: Role of the Funder/Sponsor: The funding organizations had no role in design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Underreporting of violent injuries of all causes (not just firearm injuries) has been reported as high as 83% to 93% in one recent study in Atlanta. 13 As was the case for fatal injuries, the reasons for omission from law enforcement of nonfatal injuries were multifactorial, but a primary driver is likely due to reporting requirements. Kentucky is one of nine states that does not have a statute requiring mandatory reporting of firearm injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Underreporting of violent injuries of all causes (not just firearm injuries) has been reported as high as 83% to 93% in one recent study in Atlanta. 13 As was the case for fatal injuries, the reasons for omission from law enforcement of nonfatal injuries were multifactorial, but a primary driver is likely due to reporting requirements. Kentucky is one of nine states that does not have a statute requiring mandatory reporting of firearm injuries.…”
Section: Discussionmentioning
confidence: 99%
“…They found only about 50% overlap between the two sources, suggesting many victims seeking an examination following an assault did not necessarily alert police. Wu et al (2019) attempted to match up violent injury incidents from an Atlanta trauma center to police reports from two nearby agencies over a year and a half period. They found a substantial proportion of hospital-treated injuries were not reported to police, estimating 83% of injuries did not have a matching police report in one agency and 93% in the other.…”
Section: Prior Researchmentioning
confidence: 99%
“…A recent study indicates a large difference in the number of violent injuries reported to police and treated in a trauma center, further reflecting the necessity of health system involvement. 13 Second, we only included hospitals within the city of Detroit, likely resulting in under-sampling the places in which victims of violent crime go to receive care. We also did not consider transportation times or routes that may affect the hospital receiving an injury.…”
Section: Limitationsmentioning
confidence: 99%